(untitled) (Research, Society and Development, 2022)
The emergence of resins was a great milestone for dentistry, previously when dental restorations were made using dental amalgam, in the vast majority of cases it was necessary to carry out great wear of healthy dental structures in order to obtain a cavity preparation that met the requirements of the dentist. dental amalgam. With the emergence of composite resins, this excessive wear was extinguished since this material did not require specific characteristics of preparation for its use. Over time, composite resins have undergone evolutions, including the emergence of microparticulate, microhybrid and nanohybrid resins. A review of the narrative literature on the proposed theme was carried out using scientific articles published between 2017 and 2022 as a bibliographic basis, available in the online databases BVSalud, PUBMed and Scielo, all works are available in Portuguese, English and Spanish. The search for scientific articles was performed using the expressions “Composite resins”, “Evolution of composite resins”, “Microhybrids”, “Nanoparticulates”, “composite resins”, “Evolution of composite resins”, “microhybrids” and “nanoparticulates”. Articles unrelated to the topic and/or available in languages other than Portuguese, English or Spanish were excluded. After analyzing all the material used as a bibliographic basis for the development of this work, it is concluded that the resins were an important milestone, enabling the realization of conservative and aesthetic treatments, however, it is extremely important that dental surgeons know how to perform the indication of these in cases where they are suitable for use.